Development of Creative Competence of Educators in Preschool Educational Institutions - Shoturayevna, Utasheva Lola (European Journal of Life Safety and Stability (2660-9630), 2021)
This article is about the creativity of educators in preschools qualities, improvement of methods of developing creative competence theoretical foundations are highlighted.